The influence of earnings, cash flow components and operating working capital on future cash flow of banking sector in Indonesia - Fayeno Yunanda; Islahuddin Islahuddin (Proceedings of AICS - Social Sciences, 2017)
This study is aimed at examining the influence of earnings, cash flow components and operating working capital on future cash flow of banking sector in Indonesia for the period of 2010-2014. Banking sector is considered in this study for its reputation as one of the fastest growing sector in financial services industry in Indonesia. A sample of 48 banks is drawn purposively from banking companies listed in IDX (Indonesian Stock Exchange) for the period of 2010-2014. Multiple linear regression analyses are used to test the hypotheses. The result showed that earnings, cash flow components of operating cash flow, investing cash flow, and financing cash flow, and operating working capital are simultaneously influence future cash flow. In addition, only earnings influences future cash flow, while operating cash flow, investing cash flow, financing cash flow and operating working capital has no partial influence on future cash flow.